2023
DOI: 10.1177/23259671231182968
|View full text |Cite
|
Sign up to set email alerts
|

At-Risk Tackling Techniques and Effectiveness in NCAA Division I Collegiate Football

Abstract: Background: Head-down tackling has been associated with injuries to the brachial plexus, cervical spine, and head in high school and collegiate American football. Head-down tackling has also been associated with decreased effectiveness in successful tackles compared with head-up tackling. Purpose: To assess tackling techniques used during National Collegiate Athletic Association (NCAA) Division I football games and to evaluate the successful tackling rates according to technique. Study Design: Cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
4
2
0
Order By: Relevance
“…The results of this study indicated that head-up tackles were successful in 80.7% of the tackle attempts in contrast to head-down tackles, which were successful in 71.1% of tackle attempts ( P = .0072). This was similar to findings from prior studies in American football by Stockwell et al 10 and our author group 6 indicating that head-up tackles are associated with higher success rates than head-down tackles. Moreover, in the current study, tackles made at or above the waist were successful in 80.7% of the tackle attempts compared with 73.1% of tackles below the waist ( P = .0193).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of this study indicated that head-up tackles were successful in 80.7% of the tackle attempts in contrast to head-down tackles, which were successful in 71.1% of tackle attempts ( P = .0072). This was similar to findings from prior studies in American football by Stockwell et al 10 and our author group 6 indicating that head-up tackles are associated with higher success rates than head-down tackles. Moreover, in the current study, tackles made at or above the waist were successful in 80.7% of the tackle attempts compared with 73.1% of tackles below the waist ( P = .0193).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in the current study, tackles made at or above the waist were successful in 80.7% of the tackle attempts compared with 73.1% of tackles below the waist ( P = .0193). Similarly, in our previous study on American football, 6 tackles made at or above the waist were successful in 81.2% of the tackle attempts compared with 67.2% of tackles below the waist ( P < .001). Our current analysis also found that, as with previous findings, 6 executing a head-up technique will naturally raise the point of contact with the ball carrier to deliver a tackle at or above the level of the waist.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations